On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae) - Szűts, Tamás; Zalai, Béla; Villepoux, Olivier; Buchholz, Sascha; Eichardt, János; Zhukovets, Evgeni; Oger, Pierre; Szinetár, Csaba (Zootaxa, 2017)
In this paper we propose Trebacosa brunhesi Villepoux, 2007 as a junior synonym of Trebacosa europaea Szinetár & Kan-csal, 2007 based on the examination of specimens from all the localities from where those species are known. Illustration of the type species of the genus, Trebacosa marxi (Stone, 1890) and specimens from all known localities of T. europaea are given to show both the inter- and the intraspecific differences of the genus. Scanning electron micrographs were used to illustrate the detailed structure of the female’s genitalia.